Science and the Reformation: historiographical soundings - Jordan, PN (Paternoster Periodicals, 2017)
The present article surveys some of the ways in which historians have conceived of the relations between science and the Reformation. Intended as an introduction for those unfamiliar with this literature, it focuses on a selection of studies that together illustrate something of the range of associations, interactions, and influences that historians have identified.